The Rhinella arenarum transcriptome: de novo assembly, annotation and gene prediction - Ceschin, Danilo Guillermo (2020)
The common toad Rhinella arenarum is widely distributed in Argentina, where it is utilised as an autochthonous model in ecotoxicological research and environmental toxicology. However, the lack of a reference genome makes molecular assays and gene expression studies difcult to carry out on this non-model species. To address this issue, we performed a genome-wide transcriptome analysis on R. arenarum larvae through massive RNA sequencing, followed by de novo assembly, annotation, and gene prediction. We obtained 57,407 well-annotated transcripts representing 99.4% of transcriptome completeness (available at http://rhinella.uncoma.edu.ar). We also defned a set of 52,800 highconfdence lncRNA transcripts and demonstrated the reliability of the transcriptome data to perform phylogenetic analysis. Our comprehensive transcriptome analysis of R. arenarum represents a valuable resource to perform functional genomic studies and to identify potential molecular biomarkers in ecotoxicological research.